2020
DOI: 10.3389/fcvm.2020.581211
|View full text |Cite
|
Sign up to set email alerts
|

Future Perspectives in Percutaneous Treatment of Tricuspid Regurgitation

Abstract: Tricuspid regurgitation (TR) has a not negligible prevalence and its severity is correlated with poorer outcomes. However, surgical options are rarely offered to these patients because of their high surgical risk. Given that medical therapy plays a limited role in the management of these patients, there is an increasing clinical need for transcatheter treatment options. Although, transcatheter tricuspid valve interventions (TTVIs) are still at an early stage, emerging data suggests their clinical effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Due to the high prevalence of significant TR with increasing age, many patients are further deemed as high surgical risk, leaving most of them without any other choices than conservative therapy. Thankfully, recent advancements in percutaneous technologies have created novel perspectives, but are yet lacking sufficient data to support their widespread use [ 6 ]. One of these emerging devices is the TriClip ® system, a leaflet plasty device used for reducing TR by either creating a triple-orifice or a bicuspidalized valve [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high prevalence of significant TR with increasing age, many patients are further deemed as high surgical risk, leaving most of them without any other choices than conservative therapy. Thankfully, recent advancements in percutaneous technologies have created novel perspectives, but are yet lacking sufficient data to support their widespread use [ 6 ]. One of these emerging devices is the TriClip ® system, a leaflet plasty device used for reducing TR by either creating a triple-orifice or a bicuspidalized valve [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although indications for surgical treatment of secondary tricuspid regurgitation are clearly stated in current guidelines, 9,10 isolated tricuspid valve surgery is associated with high mortality 11–13 . New transcatheter options have been developed during recent years for the percutaneous treatment of tricuspid regurgitation 14 . The randomized trial to Evaluate Cardiovascular Outcomes in Patients Treated with the Tricuspid Valve Repair System Pivotal (TRILUMINATE Pivotal) has recently demonstrated that tricuspid transcatheter edge-to-edge repair (TEER) was safe in patients with severe tricuspid regurgitation and, as compared with medical therapy, reduced tricuspid regurgitation severity and improved quality of life, although mortality and heart failure hospitalization were similar between the TEER and control groups.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] New transcatheter options have been developed during recent years for the percutaneous treatment of tricuspid regurgitation. 14 The randomized trial to Evaluate Cardiovascular Outcomes in Patients Treated with the Tricuspid Valve Repair System Pivotal (TRILU-MINATE Pivotal) has recently demonstrated that tricuspid transcatheter edge-to-edge repair (TEER) was safe in patients with severe tricuspid regurgitation and, as compared with medical therapy, reduced tricuspid regurgitation severity and improved quality of life, although mortality and heart failure hospitalization were similar between the TEER and control groups. However, the rate of clinical events was lower than expected in both arms probably because of the low-risk profile of the included population.…”
Section: Introductionmentioning
confidence: 99%
“…The cor triatriatum dexter membrane can be identified by TTE, TEE, cardiac CTA, or cardiac MRI [8,9]. The association of incomplete cor triatriatum dexter membrane and a sinus venosus ASD is very rare, and makes the percutaneous closure of ASD [8][9][10] and the percutaneous treatment of tricuspid valve regurgitation [11,12] very challenging.…”
Section: Introductionmentioning
confidence: 99%